Brain serotonin1A receptor binding measured by positron emission tomography with [11C]WAY-100635: effects of depression and antidepressant treatment. - Sargent, P; Kjaer, K; Bench, C; Rabiner, E; Messa, C; Meyer, J; Gunn, R; Grasby, P; Cowen, P (2000)
BACKGROUND: Pharmacological and postmortem investigations suggest that patients with major depressive disorder have alterations in function or density of brain serotonin1A (5-HT1A) receptors. The aim of the present study was to use positron emission tomography with the selective 5-HT1A receptor antagonist [11C]WAY-100635 to measure 5-HT1A receptor binding in depressed patients before and during treatment with selective serotonin reuptake inhibitors. METHODS: Positron emission tomographic scans with [11C]WAY-100635 were performed on 25 patients with major depressive disorder. These included 15 unmedicated depressed patients. Ten of these unmedicated patients were scanned again during selective serotonin reuptake inhibitor treatment. A further 10 patients with major depressive disorder were scanned on one occasion only while taking selective serotonin reuptake inhibitors. Comparisons were made with [11C]WAY-100635 positron emission tomographic scans in 18 healthy volunteer subjects. Region of interest analysis and statistical parametric mapping were performed on binding potential images generated using a reference tissue model. RESULTS: Binding potential values were reduced across many of the regions examined, including frontal, temporal, and limbic cortex in both unmedicated and medicated depressed patients compared with healthy volunteers. Binding potential values in medicated patients were similar to those in unmedicated patients. CONCLUSIONS: Major depressive disorder is associated with a widespread reduction in 5-HT1A receptor binding. This reduced 5-HT1A receptor binding was not changed by selective serotonin reuptake inhibitor treatment.